Assessment of Seed Storability Attributes of Selected Nigerian Rice Varieties Under Ambient Conditions in Guinea Savannah Ecology - Okelola, F. S.; Lawal, I. T; Adebisi, M. A. (Discoveries in Agriculture and Food Sciences, 2024)
Temperature and seed moisture content are the two most important factors which influence longevity of seeds in storage. Freshly harvested seeds of the 22 varieties of Nigerian cultivated rice varieties grown during 2017 cropping year at the National Agricultural Seeds Council, Abuja, a guinea savannah environment of Nigeria. Seed lot of each variety were stored under ambient humid conditions of the Seed Processing and Storage complex in NASC, Abuja Nigeria. Two factors were evaluated i.e. 22 cultivars and six storage durations (0, 60,120,180,240 and 300 days). Harvested and cleaned seeds were stored under ambient storage conditions (28 - 31oC ± 1; 70 – 72% RH) for 300 days using CRD in three replicates. The stored seeds were drawn every 60 days and tested for seed quality and longevity attributes. Data obtained were subjected to Analysis of Variance and means were separated using Tukey’s HSD at 5% probability level. Pearson’s correlation coefficient and principal component analyses were also used. PROBIT analysis was done on seed longevity. PROBIT modeling showed that seeds retained its viability, irrespective of storage time, and had very low varietal deterioration. PROBIT modeling predicted that FARO 22 and FARO 57 can be stored with good seed storage conditions for an average of 51 and 45 months, respectively, before they start deteriorating.